2015
DOI: 10.1515/agri-2015-0011
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness Of Soil Conservation To Erosion Control On Several Land Use Types

Abstract: The erosion plot method for direct evaluation in agriculture became necessary to (1) quantify soil erosion on cocoa, areca and oil palm, (2) determine the most effective soil conservation, and (3) calculate nutrient content in sediment. The experiment was treated with three conservation practices and the conventional treatment as control in a completely randomised block design. The results showed for the areca land use, that soil conservation with ridges + maize produced the lowest erosion (1.68 t/ha). For coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 7 publications
1
14
0
5
Order By: Relevance
“…The influence of the use of plants for erosion control in oil palm plantations in tropical area is also demonstrated by Satriawan et al (2015), where the use of Mucuna bracteata as cover crop plants enables to minimize erosion up to 34.61% compared with no soil conservation. Moreover, using plants for erosion control indicated benefits in controlling soil erosion in other climatic regions, similar to other previous studies by Gomez et al (2009) who reported that using cover crop with barley reduced the soil losses to 0.8 t/ha/year and the average annual runoff coefficient to 1.2%, that indicated the use of a cover crop can be a simple, feasible soil and water conservation practice.…”
Section: Soil Erosionmentioning
confidence: 97%
“…The influence of the use of plants for erosion control in oil palm plantations in tropical area is also demonstrated by Satriawan et al (2015), where the use of Mucuna bracteata as cover crop plants enables to minimize erosion up to 34.61% compared with no soil conservation. Moreover, using plants for erosion control indicated benefits in controlling soil erosion in other climatic regions, similar to other previous studies by Gomez et al (2009) who reported that using cover crop with barley reduced the soil losses to 0.8 t/ha/year and the average annual runoff coefficient to 1.2%, that indicated the use of a cover crop can be a simple, feasible soil and water conservation practice.…”
Section: Soil Erosionmentioning
confidence: 97%
“…Geographical Information System (GIS) has been widely applied in various fields, including forestry and agriculture. According to Rahmawaty et al (2012), Rahmawaty et al (2014), Rahmawaty et al (2017a), Rahmawaty et al (2017b), Rahmawaty et al (2018), Rahmawaty et al (2019a), Satriawan et al 2015, one application of GIS in the field of forestry and agriculture is mapping of land evaluation and presenting the results in the form of maps. The Geographical Information System (GIS) is used for data collection, storage, analysis and manipulation of geographic references, include layout the map to show the spatial distribution of geographical phenomena including characteristics that are in accordance with those on the surface of the earth (Rahmawaty et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Astragalus hypsogeton Bunge appropriate site.Rahmawaty et al (2016) have been used GIS for land suitability for Tectona grandis: case study in Arboretum Kwala Bekala, Sumatera Utara University Satriawan et al (2015). have been used GIS for soil conservation to erosion control on several land-use types Satriawan et al (2014).…”
mentioning
confidence: 99%
“…Hasil analisis kelas kesesuaian lahan Tectona grandis disajikan pada Tabel 3. Berdasarkan Tabel 3, pada satuan lahan I-X kelas kesesuaian lahan aktual cukup sesuai (S2) seluas 51,09 Ha (78,82% dari total luas Arboretum USU) (Tabel 4) dengan faktor penghambat curah hujan, bahaya erosi dan tambahan faktor pembatas ketersediaan oksigen/drainase pada satuan lahan I. Faktor penghambat curah hujan merupakan faktor alam yang tidak dapat diperbaiki, ketersediaan oksigen dapat diatasi dengan pembuatan saluran drainase dan bahaya erosi dapat diatasi dengan pembuatan teras, penanaman sejajar kontur, dan penanaman penutup tanah (Satriawan et al, 2015). Oleh sebab itu, kelas kesesuaian lahan potensial pada satuan lahan I-X tetap cukup sesuai (S2) dengan faktor penghambat ketersediaan air.…”
Section: Hasil Dan Pembahasanunclassified